A Systems and procedures study on the electrical and mechanical division of the Campus Planning Development Maintenance Office Erwin Alampay...[et. al]. - Alampay, Erwin; Escano, Marco; Mamutuk, Nattalie R.; Lacanaria, Sofia; Valera, Jasmin (College of Engineering, 1987)
The group has conducted a Systems and Procedures Study at the Electrical and Mechanical Division of the UP Campus Planning, Development and Maintenance Office. The group made some observations and inquiries on how their present system works, availed of all the forms the division uses and made a careful analysis on each of the forms. The group particularly noted the forms' format and design and decided to concentrate on the Job Request Form, having concluded it to be the most important form in the division. This said form is used by a requestee in making a job request. Applying their knowledge in Forms Analysis, the group made some revision concerning the Job Request Form's format with the objective of making it easier for a requestee to fill up. The group also eliminated unnecessary steps in the design by reducing its copies. The group also considered the division's system on their personnel, the working condition and the total systems in general. After a careful study, the group came up with alternatives for improvement, rate it and finally came up with the most feasible alternatives for implementation.